Nonlinear effects of gravity on earthquake response of an elastic shear-flexural building - Tingatinga, Eric Augustus J.; Kawakami, Hideji
An analytical building model that illustrates non-linear effects caused by gravity is introduced in this paper. Governing equations for the motion of one story shear flexural building subjected to earthquake induced horizontal ground motion were developed taking into account large displacements. The response of typical structures subjected to harmonic ground excitation was expressed in exact and approximate formulations. Numerical examples show that large amplitude motion contains sub-harmonic components and increasing the amount of damping significantly decreases the higher mode contribution on the response. It was also shown that gravity generally decreases the natural frequency of elastic systems and that the apparent natural frequency further decreases with ground motion amplitude.
Keywords: Shear-flexural building; Gravity-effect.; Non-linearity.